THE PROPORTION OF FAILURES OF THE HASSE NORM PRINCIPLE. Issue 2 (22nd January 2016) - Browning, T. D.; Newton, R.
Abstract : For any number field we calculate the exact proportion of rational numbers which are everywhere locally a norm but not globally a norm from the number field.